The Design and Analysis of a Modified Work Function Algorithm for Solving the On-Line k-Server Problem - Baumgartner, Alfonzo; Rudec, Tomislav; Manger, Robert (Computing and Informatics, 2012)
In this paper we study a modified work function algorithm (WFA) for solving the on-line k-server problem. Our modification is based on a moving window, i.e. on an approximate work function that takes into account only a fixed number of most recent on-line requests. We give a precise specification of the modified WFA, investigate its competitiveness, and explain how it can be implemented efficiently by network flows. We also present experiments that measure the performance and computational complexity of the implemented algorithm. The results of the paper can be summarized as follows: the modified WFA is not competitive, but according to the experiments it still provides almost the same quality of serving as the original WFA while running much faster.